JOURNAL OF GOVERNMENT & POLITICS : Transcending the Institutionalist-Interpretivist Binary; Realizing Critical Realist Theory of Governance as Metagovernance - Theerapat Ungsuchaval (FISIPOL UMY, 2016)
Governance is essentially a popular contested concept and its definition is variously applied.